The Role of Perceived Legitimacy and Its Effect on Prison Adaptation: a Longitudinal Study on a Chinese Juvenile Prison - Zhao, Jihong (International journal of offender therapy and comparative criminology, 2020)
Research into offenders' adaptation to prison environment has been a topic of enduring interest. Recently, perceived legitimacy in corrections has attracted considerable attention and emerged as an important area of research in the prison settings. The purpose of this study is to examine the factors associated with perceived legitimacy in corrections, and document its effect on juvenile offenders' adaptation to the institutional environment of a Chinese youth prison. Data for the analysis were collected from the lone youth prison located in an autonomous region with more than 47 million persons of varying ethnicity. Using structural equation modeling (SEM), the findings suggest a significant effect for perceived legitimacy on juvenile offender adaptation to prison programs. The final model was able to explain 61% of variation in the outcome variable and identify several prominent contributors to perceived legitimacy. Policy implications were highlighted in the "Discussion and Conclusion" section.